The Effectiveness of Antiplatelet Therapy in COVID-19 Patients: A Narrative Literature Review - Muhammad Ridhwan Fatharanifurqan; Rudy Afriant; Raveinal; Fauzar; Drajad Priyono (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Coagulopathy is a feature of severe COVID-19 disease and contributes to an increased risk of thromboembolic complications and death. This literature review aimed to describe the effectiveness of antiplatelet therapy in COVID-19 patients. There is an inverse relationship between the likelihood of COVID-19 infection, duration of illness and death, and use of antiplatelets for primary prevention. A study showed that COVID-19 patients who did not receive antiplatelet drugs had three times the risk of dying with antiplatelet drugs. This study shows the strong effect of antiplatelet drugs on reducing the mortality rate of COVID-19 patients. Another study showed that COVID-19 patients who received antiplatelet drugs had 1.18 times the risk of dying than those without antiplatelet drugs. This study shows that antiplatelet therapy does not affect the reduction in mortality in patients hospitalized with COVID-19. In conclusion, the effectiveness of antiplatelet administration in COVID-19 patients is still unclear, so further research is needed.